Ultrasound-guided single needle tip placement below axillary artery in the infraclavicular area: A cadaveric study - Sandeep Diwan; Georg Feigl; Abhijit Nair (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: The parasagittal ultrasound-guided infraclavicular block (ICB) aims to cover all the elements of brachial plexus for the surgeries at and below the elbow. Our aim was to demonstrate the spread of 20 ml latex in vicinity of brachial plexus cords after injecting posterior to the axillary artery in Thiel embalmed cadavers. Material and Methods: A blunt insulated needle was inserted posterior to the axillary artery in a traditional parasagittal infraclavicular in 2 Thiel embalmed cadavers, on both the sides (four specimens). A day later cadaver 1 was dissected and cadaver 2 was frozen at ‒20°C for 2 weeks and sectioned. Both cadavers were photographed. Results: In cadaver 1, dissection revealed a spread of red latex on the lateral cord extending onto the musculocutaneous nerve, the posterior cord engulfing the radial and axillary nerves distally. In cadaver 2, a cross-section revealed latex engulfed all three cords. Conclusion: Single injection of 20 ml latex aimed posterior to the axillary artery in the parasagittal infraclavicular approach engulfed the posterior, medial and lateral cord in Thiel embalmed cadavers. This needs to be investigated in patients who receive ICB clinically and using contrast studies.